S=1/5(65-5e)

Simple and best practice solution for S=1/5(65-5e) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for S=1/5(65-5e) equation:


S in (-oo:+oo)

S = (1/5)*(65-(5*e)) // - (1/5)*(65-(5*e))

S-((1/5)*(65-(5*e))) = 0

S+(-1/5)*(65-5*e) = 0

S-1/5*(65-5*e) = 0 // + -1/5*(65-5*e)

S = -(-1/5*(65-5*e))

S = 1/5*(65-5*e)

S = 1/5*(65-5*e)

See similar equations:

| 5x-3+3x+45=90 | | 4x-18+90=180 | | y=(x+3)(x^2+25)(x^2-2x+10) | | -3(4-a)=-15 | | -2n-12=-6(2+6n) | | 96=15+9s | | 5x+6(-2+18)=157 | | 5(n+3)=3(2*n-1) | | 8y-3y=35 | | 5x+6(-2+18)=108 | | 4y=3x+C | | 63/w=9 | | 12x=5(8+2x) | | h=-2(t-1)-16t(t-1) | | XP+to=z | | 8m+10=50 | | 4(x-5)+6=2(2x-7) | | x*5+65=4*x | | 24+5h=89 | | 10x-3/12 | | X^2-9x-19/x-2 | | 2x-54=104 | | 2(x+3)+x+7=2(3x+9)+5(4-x)+3 | | 4(3x+8)=32 | | 9x+4=5x+2 | | -3(x-4)+5=-2z-2 | | 5x^4=20x^6 | | 10d+6-6d=22 | | -3(x+8)=-15 | | -5(2.5+x)=10 | | -9x^2+120x-12=0 | | -1(-3x-5)=-7 |

Equations solver categories